Legal Protection of Bambu Gila Dance as a Traditional Cultural Expression - Berlianty, Teng; Hetharie, Yosia; Putri Anggia (Universitas Airlangga, 2024)
This study aims to examine the bambu gila dance as a potential intellectual property for traditional cultural expressions in Maluku which should receive legal protection as part of efforts to defend cultural heritage from claims of ownership by other parties or other countries. Bambu Gila Dance is one of the famous traditional arts from Maluku. The traditional cultural expression in the form of the Bambu Gila dance is expressly protected by the Indonesian intellectual property rights system. However, protection for Bambu Gila Dance as a traditional cultural expression cannot be realized so that it can only be used by other parties illegally. This research is a normative juridical research supported by primary legal materials and secondary legal materials with a conceptual approach and statutory approach. Legal protection for the traditional Bambu Gila dance from Maluku Province has not been effectively implemented, both based on Article 38 of Law Number 28 of 2014 Concerning Copyright, as well as in terms of the actions of government officials who have not been able to inventory traditional dance performance artworks as an expression traditional culture in Maluku including the Bambu Gila Dance. The role of the Provincial and Regency Governments in Maluku is crucial in realizing legal protection for traditional dances, including the Bambu Gila Dance, as intangible cultural heritage through the establishment of regional regulations. These regulations serve as legal basic to provide legal certainty as part of efforts for preventive legal protection for the Bambu Gila Dance.